India’s Publications on Rheumatoid Arthritis: A Bibliometric Analysis of Research Output from 1994 to 2023 A.D. - Vaishya, Raju; Gupta, Brij Mohan; Mamdapur, Ghouse Modin Nabeesab; Ali, KS; Vaish, Abhishek (Journal of Nepal Health Research Council, 2024)
Background: Over the years, several studies have been conducted by utilizing bibliometric techniques to reveal research trends in various sub-fields of medical sciences, including arthritis research. Although no bibliometric study has been conducted at the global level on RA, bibliometric studies do exist in the Indian situation. Methods: In this study, we examined the publications of Indian scholars on Rheumatoid Arthritis (RA) in the last three decades, using various quantitative and qualitative bibliometric indicators. The publications on RA (from 1994-2023) in the Scopus database were identified, analysed and evaluated using a pre-defined search strategy, and specialised software. Results: 1603 papers were published on RA research that was cited 36814 times (averaging 11.48 citations per paper or CPP). The 18.65% and 16.71% of India’s total publications indicated received external funding. The most productive Indian organizations were AIIMS, (New Delhi), SGPGIMS (Lucknow) and PGIMER (Chandigarh). The most impactful organizations were AMU (Aligarh), Fortis Healthcare Ltd. (Gurgaon), and Punjab University (Chandigarh). The most productive authors were A. Aggarwal, R. Misra, A. Chopra and U. Kumar. The most impactful authors were A. Aggarwal, A. Ghosh, S. Shankar, R. Misra. Medicine (64.2% share), Pharmacology, Toxicology and Pharmaceutics (22.0% share), Biochemistry, Genetics and Molecular Biology (19.8% share) and Immunology & Microbiology (12.8% share) contributed the most publications in this area. Clinical studies (40.9% share), pathophysiology (13.2% share) and the treatment outcome (9.0% share) accounted maximally. The most significant keywords appearing in the area were: “Rheumatoid Arthritis”, “Methotrexate”, and “Rheumatoid Factor”. Conclusions: This study provides insight into past, present, and future areas of India on research in RA and will help scholars identify the areas of collaboration. Keywords: Bibliometric; highly cited papers; India; research; rheumatoid arthritis.